The Effect of Product Quality, Price and Sales Location of Nugin Lamping Tofu on Consumer Satisfaction - Mia Nur Yanti; Mutia Intan Savitri Herista (Jurnal Impresi Indonesia, 2024)
Tofu lanting nuggets are one type of snack food that is very popular with the public. Along with increasing consumer awareness of product quality, competition in the lanting tofu market is getting tougher. The focus of the study aims to determine the extent to which "the influence of product quality, price and sales location of Tahu Lamping Nugin" plays a role in influencing the level of customer satisfaction. This research was conducted using quantitative as a research method. Meanwhile, data collection was carried out involving questionnaire surveys and other literature studies. After the data was collected, it was analyzed using the regression test using SPSS software. The conclusion from the results of the research analysis shows that product quality, price and sales location of Lamping Nugin Tahu have an effect on customer satisfaction. In an effort to achieve an optimal level of customer satisfaction, companies need to focus on maintaining and improving product quality and determining prices that remain balanced with the value offered. Meanwhile, the sales location is still important to attract consumer interest, but this needs to be balanced by offering products of good quality and reasonable prices.